2021
DOI: 10.1001/jamasurg.2021.4412
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Paradigm for Surgical Skills Training and Assessment of Competency

Abstract: Sustainment of comprehensive procedural skills in trauma surgery is a particular problem for surgeons in rural, global, and combat settings. Trauma care often requires open surgical procedures for low-frequency/high-risk injuries at a time when open surgical experience is declining in general and trauma surgery training.OBJECTIVE To determine whether general surgeons participating in a 2-day standardized trauma skills course demonstrate measurable improvement in accuracy and independent performance of specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…An increase in self-efficacy in trauma management skills after the trauma masterclass participation is in line with the preceding research among participants of the DSATC courses between 2013 and 2016, the ASSET, ATOM, and Norwegian trauma course [8][9][10]12]. Remarkably, Ali et al found that knowledge on trauma management measured on a multiple-choice test did not improve as much as expected after the ATLS course [9].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…An increase in self-efficacy in trauma management skills after the trauma masterclass participation is in line with the preceding research among participants of the DSATC courses between 2013 and 2016, the ASSET, ATOM, and Norwegian trauma course [8][9][10]12]. Remarkably, Ali et al found that knowledge on trauma management measured on a multiple-choice test did not improve as much as expected after the ATLS course [9].…”
Section: Discussionsupporting
confidence: 82%
“…Various courses have been developed to provide alternative training opportunities in trauma care, beyond the basic principles of the Advanced Trauma Life Support (ATLS). The Advanced Surgical Skills for Exposure in Trauma (ASSET), Advanced Trauma Operative Management (ATOM), Definitive Surgical and Anesthetic Trauma Care (DSTC and DATC), and Norwegian trauma courses have demonstrated a correlation with greater trauma skills and self-efficacy levels [8][9][10][11][12][13]. However, the educational rationale on how these teaching formats enhance domainspecific skills and self-efficacy in the workplace has been insufficiently explored.…”
Section: Introductionmentioning
confidence: 99%
“…2 Independent of learning modality, the fundamental foundation for training success both in and outside of the operating room still lies in the assessment. 3 In this issue of JAMA Surgery, using cadavers, procedurespecific assessments, and coaching, Bowyer et al 4 found that general surgeons (N = 65) with no prior trauma training could be trained to a proficiency benchmark for 24 trauma skills during a 2-day course. A major feature of the course was realtime formative and summative assessments combined with one-on-one meetings with coaches to review performance assessment details.…”
Section: Carla M Pugh Md Phdmentioning
confidence: 99%
“…The UK Defence Medical Services (DMS) and our allies recognise the difficulties associated with acquisition and retention of militarily relevant surgical knowledge, skills and abilities among their surgical cadres 3–6. Training opportunities have been limited by factors such as the limited penetrating trauma workload in non-deployed roles,4 interruptions to training during the COVID-19 pandemic,7 and reduced deployed experience since the cessation of combat operations in Iraq and Afghanistan.…”
Section: Introductionmentioning
confidence: 99%